2020
DOI: 10.1177/0271678x20950489
|View full text |Cite
|
Sign up to set email alerts
|

MiR-17-92 enriched exosomes derived from multipotent mesenchymal stromal cells enhance axon-myelin remodeling and motor electrophysiological recovery after stroke

Abstract: MiR-17-92 cluster enriched exosomes derived from multipotent mesenchymal stromal cells (MSCs) increase functional recovery after stroke. Here, we investigate the mechanisms underlying this recovery. At 24 h (h) post transient middle cerebral artery occlusion, rats received control liposomes or exosomes derived from MSCs infected with pre-miR-17-92 expression lentivirus (Exo-miR-17-92+) or control lentivirus (Exo-Con) intravenously. Compared to the liposomes, exosomes significantly reduced the intracortical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 67 publications
(78 reference statements)
1
53
0
Order By: Relevance
“…Exosomes are extracellular vesicles that transport proteins, miRNAs, lncRNAs, and circRNAs to remotely regulate physiological and pathological processes 14 . Studies show that exosomes derived from endothelial progenitor cells, adipose‐derived stem cells, and multipotent mesenchymal stromal cells can manifest neuroprotective or neurotrophic effects by transporting protective miRNAs 23‐25 . Consistent with this, the plasma exosomes of sham‐operated and cerebral‐IPC mice in our study showed distinct miRNA profiles.…”
Section: Discussionsupporting
confidence: 85%
“…Exosomes are extracellular vesicles that transport proteins, miRNAs, lncRNAs, and circRNAs to remotely regulate physiological and pathological processes 14 . Studies show that exosomes derived from endothelial progenitor cells, adipose‐derived stem cells, and multipotent mesenchymal stromal cells can manifest neuroprotective or neurotrophic effects by transporting protective miRNAs 23‐25 . Consistent with this, the plasma exosomes of sham‐operated and cerebral‐IPC mice in our study showed distinct miRNA profiles.…”
Section: Discussionsupporting
confidence: 85%
“…Further studies are clearly desirable to decipher the underlying mechanisms. Besides the neurotrophin and immune regulation, 41 emerging evidence has shown that MSC transplantion can protect and improve the neuron function after injury via exosomes 42 and mitochondrial transfer 43 . Notwithstanding of the above, it is suggested that MN+EA treatment as demonstrated in the present study can repair the SCI effectively which is likely through multiple effects.…”
Section: Discussionmentioning
confidence: 60%
“…Mesenchymal stem cells (MSCs) pose as a potential source for transplantable cells as evidenced by their therapeutic effects in rat and mouse HIE models. 10 The postulated mechanism of MSCs implicates trophic effects delivered by cytokines and nutritional factors, 11,12 but the transplanted cells display only transient engraftment into the host tissue, thereby preventing long-term therapeutic effects. 13 Multilineage-differentiating stress enduring cells (Muse cells), harvested from bone marrow (BM), blood and organ connective tissues, display endogenous pluripotent-like property and express pluripotent surface marker stage-specific embryonic antigen-3 (SSEA-3).…”
Section: Introductionmentioning
confidence: 99%